Histopathological evaluation of microwave tissue coagulation for rat liver tumor - Sawamura, Akihiro; Toge, Tetsuya; Aogi, Kenjiro; Yoshimoto, Akihiro; Kuniyasu, Hiroki; Tahara, Eiichi (Journal of Microwave Surgery, 1996)
Purpose of this study was to evaluate the effectiveness of microwave tissue coagulation (MTC) therapy at low out put irradiation in the management of the malignant liver tumor. The liver tumor of the rat was irradiated at the out put of 50 watts for 30 seconds ; Group C, 10 watts for 30 seconds ; Group B and 10 watts for 15 seconds ; Group A at a time. In all of the groups, DNA damage was observed in histological findings with ethidium bromide. Any effect of MTC was not recognized in Group B and C in histological findings with hematoxylin-eosine (H-E) dyeing, however. Furthermore, cytostatic change was observed with dye exclusion test in group B and C. Thus, it suggests that the liver tumor after MTC is damaged satisfactorily at low out put irradiation, Even if it is judged that the cell viability is retained in histological findings with H-E dyeing.